Extracellular Lipases of Yarrowia lipolytica Yeast in Media Containing Plant Oils—Studies Supported by the Design of Experiment Methodology - Agata Fabiszewska; Bartłomiej Zieniuk; Karina Jasińska; Dorota Nowak; Katarzyna Sasal; Joanna Kobus; Urszula Jankiewicz (Applied Sciences)
Lipases are enzymes of great application importance in the food industry, in the cosmetic and detergent industries, in pharmacy and medicine, and in organic chemistry. Among lipases of various origins, those from microorganisms are currently the most commonly used. An excellent producer of lipases seems to be the nonconventional Yarrowia lipolytica yeast, but the biosynthesis of valuable metabolites depends on many factors. This study aimed to investigate the biodiversity of extracellular enzymes produced by four strains of Y. lipolytica, and to determine the optimal conditions of catalysis for the enzymes, according to temperature and pH, in a model hydrolysis reaction. Based on the obtained results, the biodiversity and strain dependence in lipase biosynthesis were observed. Using a Central Composite Design, it was found that temperature is the main factor in determining lipase activity. The enzymes produced by four different strains exhibited other substrate specificity, which was investigated using Latin square design methodology. Only two examined yeast strains, KKP 379 and W29, produced extracellular lipases at a high activity level towards medium- and long-chain fatty acid esters. Moreover, extracellular lipase from wild-type strain KKP 379 was further characterized, followed by exploring the activity of whole-cell biocatalyst and lyophilized enzyme solutions, and it was acknowledged that it was a “true” lipase with the highest affinity to p-nitrophenyl oleate.